2022
DOI: 10.1007/s12144-022-03153-4
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the role of interoceptive sensibility in alexithymia, emotion dysregulation, and depression in healthy individuals

Abstract: Interoception, a multifaceted concept defined as the perception of internal bodily signals, is crucially involved in mental health in general and in emotion regulation in particular, being interoceptive sensibility (IS) one of the most studied interoceptive processes. The main objective of this study was to explore the relationships between IS and emotion regulation processes, analyzing the role of the eight IS dimensions assessed by the Multidimensional Assessment of Interoceptive Awareness-2 (MAIA-2) in alex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
2
9
1
Order By: Relevance
“…These associations are consistent with previous studies showing that trusting in bodily sensations is one of the interoceptive sensibility aspects that has been most consistently related to decreased emotional disturbances and greater well-being in different populations (Brown et al, 2017;Zamariola et al, 2018;Schmitz et al, 2021). Moreover, not distracting from and not-worrying about uncomfortable bodily signals was associated with lower emotion dysregulation, which is also congruent with the findings by Desdentado et al (2023). Taken together, these findings are in line with the existing evidence on the positive effects of mindfulness-based approaches on emotional processing (Wu et al, 2019), given that some core components of mindfulness refer to attending to the present experience and bodily states with a non-judgmental attitude even if they are unpleasant (as opposed to experiencing it as something to worry about or be wary of).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These associations are consistent with previous studies showing that trusting in bodily sensations is one of the interoceptive sensibility aspects that has been most consistently related to decreased emotional disturbances and greater well-being in different populations (Brown et al, 2017;Zamariola et al, 2018;Schmitz et al, 2021). Moreover, not distracting from and not-worrying about uncomfortable bodily signals was associated with lower emotion dysregulation, which is also congruent with the findings by Desdentado et al (2023). Taken together, these findings are in line with the existing evidence on the positive effects of mindfulness-based approaches on emotional processing (Wu et al, 2019), given that some core components of mindfulness refer to attending to the present experience and bodily states with a non-judgmental attitude even if they are unpleasant (as opposed to experiencing it as something to worry about or be wary of).…”
Section: Discussionsupporting
confidence: 92%
“…This framework highlights the relevance of interoceptive sensibility dimensions involving a non-judgmental, accepting attitude and appraisal towards bodily sensations over their subjective noticing in purely quantitative terms. Consistent with this theoretical proposal, a recent study conducted on healthy participants showed that MAIA dimensions that emphasize the adaptive appraisal of interoceptive cues play a relevant role in explaining depressive symptomatology through the mediating role of alexithymia and difficulties in emotion regulation ( Desdentado et al, 2023 ). Specifically, it was found that not-distracting from and not-worrying about uncomfortable bodily sensations, as well as trusting one’s bodily cues and being able to voluntarily focus on them ( attention regulation ) were related to lower alexithymia, which in turn led to lower depressive symptomatology.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Unlike all other variables that showed a negative association, accept and notice showed a positive association with depression and anxiety, proposing that high levels of accept and notice may be risk factors depending on the pathological context in which each is manifested. Though many studies suggest that there’s a negative association between the accept subscale and depression [ 54 , 55 ], there may be some situations in which accept leads to passivity or inaction. For example, when an individual experiences bodily sensations that are consistently negative and distressing, such as fatigue, yet does not take action to address the underlying causes of this sensation, it could result in negative consequences, including continued emotional distress, decreased motivation to make positive changes, and a sense of helplessness or hopelessness.…”
Section: Discussionmentioning
confidence: 99%
“…The disturbance of interoception in MDD may result from an inefficient internal model and unreliable prediction errors (19). Using the structural equation model, a study demonstrated that low levels of interoceptive awareness lead to alexithymia and emotional dysregulation, which in turns predict depression risk (20); this study used a self-report questionnaire to assess interoceptive awareness, namely, the Multidimensional Assessment of Interoceptive Awareness-2 (MAIA-2) (21). In contrast to the aforementioned study, which collected subjective questionnaire data using the MAIA-2, we recorded objective neurophysiological data.…”
Section: Introductionmentioning
confidence: 99%